The Role of Formative Assessment in Developing English Language Curriculum and Learning - Ningsih, Nurul Rahayu; Rosidah, Nur Aini Rosidah; Pradana, Dian Arief (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research examines the role of formative evaluation in improving curriculum development and the English language learning process. Formative assessment (FA) is a comprehensive evaluation method that provides feedback to teachers and students to improve teaching effectiveness. It helps students understand their limitations and gives teachers the ability to tailor lessons to students' needs. This article uses a systematic literature review approach to collect data from various studies. The results show that formative approaches are effective in increasing students' motivation, engagement and response to learning, as well as facilitating curriculum fulfillment based on students' needs. Formative assessment can be conducted using many strategies, such as questioning, group discussions, presentations, and the use of rubrics, journals, and quizzes, supported by technology to improve efficiency and effectiveness.